Aktivitas Hepatoprotektif Ekstrak Metanol Buah Lakum (Cayratia trifolia (L.) Domin) Terhadap Diameter Vena Sentralis, Lebar Sinusoid dan Berat Hepar Tikus Putih (Rattus novergicus L.) yang Diinduksi Parasetamol - Ari Hepi Yanti, Rizki Perdana Putri Diah Wulandari Rousdy (Jurnal Protobiont, 2018)
Secondary metabolites of lakum (Cayratia trifolia (L.) Domin) fruit have been evaluated in previous researches. The fruit contains flavonoids, terpenoids and phenols which have antioxidant properties. The aim of this research was to determine the hepatoprotective activity of methanolic extract of lakum fruit in Wistar rats’ liver induced by high doses of paracetamol. Ripe lakum fruits were macerated with methanol as the solvent. Thirty-five male Wistar rats (Rattus novergicus L.) were used in this research and devided into 7 groups (normal, negative, positive, solvent, 115 mg kg-1, 230 mg kg-1, and 345 mg kg-1 of lakum fruit methanolic extract). Results showed that the effect of 230 mg kg-1 of lakum fruit methanolic extract (central vein diameter: 40,20 ± 6,97 µm; sinusoid wide: 5,60 ± 0,94 µm; and liver weight: 6,33 ± 0,98 g) were similar to the effect of silymarin (central vein diameter: 42,99 ± 6,60 µm; sinusoid wide: 4,49 ± 0,44 µm; and liver weight: 6,58 ± 0,88 g) as the standard drug.